Single center experience on dosing and adverse events of recombinant factor seven use for bleeding after congenital heart surgery - Kurkluoglu, Mustafa (Journal of the Saudi Heart Association, 2015)
There are limited data on the relationship between the administered dose of recombinant factor seven (rFVIIa) and the development of adverse clinical outcomes after congenital heart surgery. This single institution case series reports on dosing, adverse events, and blood product usage after the administration of rFVIIa in the congenital heart surgery patient population. A retrospective review identified 16 consecutive pediatric patients at an academic, free-standing, children's hospital who received rFVIIa to curtail bleeding following congenital heart surgery between April 2004 and June 2012. Patients were assessed for survival to hospital discharge versus in-hospital mortality and the presence or absence of a major neurological event during inpatient hospitalization. The median age at surgery was 6.8 months (range: 3 days-42 years). Seven patients (44%) survived to hospital discharge and nine patients (56%) died. The cause of mortality included major neurological events (44%), uncontrolled bleeding (33%), and sepsis (23%). Eight patients (50%) required extracorporeal membrane oxygenation support following congenital heart surgery. The median cumulative rFVIIa dose administered was 97 mcg/kg, and the median cumulative amount of blood products administered was 452 ml/kg. In conclusion, this case series underscores the need to prospectively evaluate the effect that rFVIIa has on patient survival and the incidence of adverse events, including thrombotic and major neurological events, in congenital heart surgery patients. Ideally, a randomized, multicenter study would provide the sufficient numbers of patients and events to test these relationships